Zirconia Nanoparticles Induce HeLa Cell Death Through Mitochondrial Apoptosis and Autophagy Pathways Mediated by ROS - Shang, Yinghui; Wang, Qinghai; Li, Jian; Liu, Haiting; Zhao, Qiangqiang; Huang, Xueyuan; Dong, Hang; Chen, Wansong; Gui, Rong; Nie, Xinmin (Frontiers in Chemistry, 2021)
Zirconia nanoparticles (ZrO2 NPs) are commonly used in the field of biomedical materials, but their antitumor activity and mechanism is unclear. Herein, we evaluated the anti-tumor activity of ZrO2 NPs and explored the anti-tumor mechanism. The results of in vitro and in vivo experiments showed that the level of intracellular reactive oxygen species (ROS) in Hela cells was elevated after ZrO2 NPs treatment. Transmission electron microscopy (TEM) showed that after treatment with ZrO2 NPs, the mitochondria of Hela cells were swollen accompanied with the induction of autophagic vacuoles. In addition, flow cytometry analysis showed that apoptotic rate of Hela cells increased significantly by Annexin staining after treatment with ZrO2 NPs, and the mitochondrial membrane potential (MMP) was reduced significantly. The proliferation of Hela cells decreased as indicated by reduced Ki-67 labeling. In contrast, TUNEL-positive cells in tumor tissues increased after treatment with ZrO2 NPs, which is accompanied by increased expression of mitochondrial apoptotic proteins including Bax, Caspase-3, Caspase-9, and Cytochrome C (Cyt C) and increased expression of autophagy-related proteins including Atg5, Atg12, Beclin-1 and LC3-II. Treating Hela cells with N-acetyl-L-cysteine (NAC) significantly reduced ROS, rate of apoptosis, MMP, and in vivo anti-tumor activity. In addition, apoptosis- and autophagy-related protein expressions were also suppressed. Based on these observations, we conclude that ZrO2 NPs induce Hela cell death through ROS mediated mitochondrial apoptosis and autophagy.